2013
DOI: 10.1111/tbed.12099
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisat the Human/Wildlife Interface in a High TB Burden Country

Abstract: Summary This study reports on an investigation of Mycobacterium tuberculosis cases in mostly captive wild animals using molecular typing tools [Variable Number of Tandem Repeat (VNTR) typing and Restriction Fragment Length Polymorphism typing]. The investigation included cases from (i) the National Zoological Gardens of South Africa (NZG) recorded between 2002 and 2011; (ii) Johannesburg Zoo, where tuberculosis was first diagnosed in 2007 and has since been detected in three antelope species; (iii) a rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 10 publications
(13 reference statements)
1
23
0
Order By: Relevance
“…Outbreaks in both feral (Keet et al 2000;Michel et al 2013) and captive (Schroeder 1938;Benson et al 1955;Mayhall et al 1981;Fourie and Odendaal 1983;Shin et al 1995;Panarella and Bimes 2010;Payne et al 2011) colonies have been reported. All NHP species are considered potentially susceptible to M. tuberculosis infection (Good 1984), with a general susceptibility hierarchy of Old World species (most susceptible), followed by apes, and New World monkeys (least susceptible) (Montali et al 2001).…”
Section: Historical Use Of Nhps In Tb Researchmentioning
confidence: 99%
“…Outbreaks in both feral (Keet et al 2000;Michel et al 2013) and captive (Schroeder 1938;Benson et al 1955;Mayhall et al 1981;Fourie and Odendaal 1983;Shin et al 1995;Panarella and Bimes 2010;Payne et al 2011) colonies have been reported. All NHP species are considered potentially susceptible to M. tuberculosis infection (Good 1984), with a general susceptibility hierarchy of Old World species (most susceptible), followed by apes, and New World monkeys (least susceptible) (Montali et al 2001).…”
Section: Historical Use Of Nhps In Tb Researchmentioning
confidence: 99%
“…MT has been isolated from antelopes from zoo and game farms in South Africa (Michel et al 2013), however, there are no such reports from India so far. An important emerging concern is not whether infection of wildlife species with MT is novel, but recent observations that MT isolates recovered from humans and members belonging to Bovidae from the same geographical area share identical spoligotypes and VNTR-MIRU profiles (Malama et al 2014;Romero et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Infection of wild species with MT in captivity is not a novel observation (Montali et al 2001) and neither is isolation of MT from antelopes (Michel et al 2013). MT has been isolated from antelopes from zoo and game farms in South Africa (Michel et al 2013), however, there are no such reports from India so far.…”
Section: Resultsmentioning
confidence: 99%
“…Where human/livestock/wildlife interactions led to the transmission and spread of MTBC to multiple species including zoonotic TB, genetic typing provided a valuable tool to generate evidence for and study inter-species and transboundary transmission of MTBC strains (Dawson et al 2012;Michel et al 2013;MilianSuazo et al 2010;Adesokan et al 2012;Vosloo et al 2001;de Garine-Wichatitsky et al 2010;Michel et al 2009;Deresa et al 2013;Etchechoury et al 2010;MilianSuazo et al 2010b;Moonan et al 2009;Kazwala et al 2006;Gibson et al 2004;Michel and Huchzermeyer 1998).…”
Section: Molecular Tools In Epidemiological Investigationsmentioning
confidence: 99%